A new chance for private pension saving? - Markus Demary; Susanna Kochskämper (Institut der deutschen Wirtschaft (IW), 2017)
The European Commission aims at strengthening the cross-border provision of pension products by the introduction of Pan-European Personal Pensions (PEPP) as a new regime on top of existing national frameworks. However, a pre-requisite for the success of PEPP will be the support of the national legislators for this framework.
Keywords: 330